Expressivite derivationnelle enfranęais contemporain: noms d’action - Kortas, Jan (Studia Romanica Posnaniensia, 2003)
This article is devoted to the problems of expressiveness of nomina actionis in some language registers of modern French. The author distinguishes two types of phenomena in the analysed category: nomina actionis which are primarily expressive and nomina actionis which are contextually expressive.